The Influence of Work-Life Balance, Organizational Support, and Jobe Stress on Employee Retention - Rachmad Ilham; Rian Pramana Suwanda; Alfred Heriman Setio; Suryaningsih; Duladi (PT. Maju Malaqbi Makkarana, 2026)
Employee retention has become a critical concern for organizations because high employee turnover can reduce organizational productivity, increase recruitment and training costs, and negatively affect overall organizational performance. This study aimed to examine the influence of work-life balance, organizational support, and job stress on employee retention. A quantitative research approach with an explanatory research design was employed to investigate the relationships among the research variables. Data were collected through a structured questionnaire distributed to 150 employees selected using an appropriate sampling technique. The research instrument utilized a five-point Likert scale to measure work-life balance, organizational support, job stress, and employee retention. The collected data were analyzed using descriptive statistics, validity and reliability tests, classical assumption tests, and multiple linear regression analysis with the assistance of Statistical Package for the Social Sciences (SPSS). The illustrative findings indicated that work-life balance has a positive and significant influence on employee retention, organizational support has a positive and significant influence on employee retention, and job stress has a negative and significant influence on employee retention. Furthermore, the three independent variables simultaneously have a significant influence on employee retention and explain a substantial proportion of the variation in employee retention. Among the independent variables, organizational support was identified as the strongest predictor of employee retention. The findings suggest that organizations seeking to improve employee retention should develop comprehensive human resource management strategies by promoting work-life balance, strengthening organizational support, and implementing effective job stress management practices. Such initiatives are expected to enhance employee well-being, increase organizational commitment, reduce turnover intentions, and contribute to long-term organizational sustainability